2011
DOI: 10.1007/s11136-011-9865-z
|View full text |Cite
|
Sign up to set email alerts
|

Personal factors associated with health-related quality of life in persons with morbid obesity on treatment waiting lists in Norway

Abstract: PurposeTo explore relationships of socio-demographic variables, health behaviours, environmental characteristics and personal factors, with physical and mental health variables in persons with morbid obesity, and to compare their health-related quality of life (HRQoL) scores with scores from the general population.MethodsA cross-sectional correlation study design was used. Data were collected by self-reported questionnaire from adult patients within the first 2 days of commencement of a mandatory educational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 45 publications
5
50
1
4
Order By: Relevance
“…Therefore, it should not be assumed that life satisfaction shares associations with mental health. Moreover, our finding that PA was not associated with mental health is in line with the study by Lerdal et al on severely obese waiting-list patients [18], whereas Martin et al found such a relation in their sample of overweight to obese sedentary women [19]. In the original studies reviewed by Bize et al the associations between PA and mental health were inconsistent between studies, and, as mentioned, the authors did not include BMI as a variable in the review [25].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it should not be assumed that life satisfaction shares associations with mental health. Moreover, our finding that PA was not associated with mental health is in line with the study by Lerdal et al on severely obese waiting-list patients [18], whereas Martin et al found such a relation in their sample of overweight to obese sedentary women [19]. In the original studies reviewed by Bize et al the associations between PA and mental health were inconsistent between studies, and, as mentioned, the authors did not include BMI as a variable in the review [25].…”
Section: Discussionsupporting
confidence: 93%
“…This study is part of a prospective longitudinal cohort study designed to evaluate 12 instruments assessing illness perceptions and coping strategies with regard to their ability to detect change over time and to explore changes in health-related quality of life among persons participating in patient education courses in Norway (Lerdal et al, 2011). The purpose of the present study was to explore the one-year trajectories of illness perceptions in persons with morbid obesity and in persons with COPD following their participation in a patient education course.…”
Section: Purposementioning
confidence: 99%
“…We excluded from our analysis morbid obesity populations (Lerdal et al 2011), child obesity (Johnson et al 2012), and erderly populations (Kuo et al 2011), to focus on how class I obesity may have an effect on mental health in adult populations.…”
Section: Selection Of Studiesmentioning
confidence: 99%